Redistributive effects of the US pension system among individuals with different life expectancy - Miguel Sanchez-Romero; Alexia Fürnkranz-Prskawetz (Vienna University of Technology, Institute of Statistics and Mathematical Methods in Economics, Research Group Economics, 2017)
We investigate the differential impact that pension systems have on the labor supply and the accumulation of physical and human capital for individuals that differ by their learning ability and levels of life expectancy. Our analysis is calibrated to the US economy using a general equilibrium model populated by overlapping generations, in which all population groups interact through the pension system, the labor market, and the capital market. Within our framework we analyze the redistributive and macroeconomic effects of a progressive versus a flat replacement rate of the pension system.
Keywords: E24; J10; J18; H55; 330; Human capital; Longevity; Inequality; Life cycle; Social Security